PRODUK PERTANIAN ORGANIK DI INDONESIA: TINJAUAN ATAS PREFERENSI KONSUMEN INDONESIA TERHADAP PRODUK PERTANIAN ORGANIK LOKAL - Melisa Khorniawati (Kompetensi (Competence : Journal of Management Studies), 2014)
Health becomes the most important and searchable, because more diseases appear and attack people. Many diseases that appears partly due to the unhealthy and unhygienic foods. Most of the people are starting to realize the importance of health and then switch to healthier foods such as organic food products. Organic food products are believed to be good for health and environmentally friendly. But, the price of organic agricultural products are more expensive so make some people prefer non-organic products. For people who have high awareness of health and the environment (green consumer) are willing to pay more to buy organic products. The difficulty of finding the desired product, the lack of information and limited places that sell organic products is another constraints besides the price factor that causes people not choose organic products. The necessity increasing the number of organic farmers in Indonesia can be one of the solutions to overcome existing constraints, because by increasing number of organic’s farmer also increase the amount of the availability of organic agricultural products so it can meet market demand and lower prices.